Novel protection approach for MV microgrid - Voima, Sampo; Kauhaniemi, Kimmo; Laaksonen, Hannu (CIRED, 2011)
The amount of distributed generation (DG) connected to medium voltage (MV) networks is expected to increase continuously. This trend creates a good opportunity to use MV feeders as microgrids. Normally microgrids will be operated parallel with the utility grid. However, for example during outages in utility grid they are capable of operating in an island mode. Nevertheless, island operation produces challenges for protection. Traditionally MV network has been protected against short-circuit faults with overcurrent relays. In island operation these relays may fail to detect fault conditions due to drastically changed network parameters and lack of short-circuit power. Above-mentioned issuescreate need to develop new protection concept for MV microgrids. The aim of this paper is to address these issues and to present an adaptive protection approach for MV microgrids based on telecommunication.
Keywords: electrical power networks; distribution of electricity; defects; distributed generation; transmission of electricity; supply of electricity; automation; parallel publishing; Finland; electric machines; fi=Sähkötekniikka|en=Electrical Engineering|